Detecting and managing the mechanism of perceived meaningfulness of work and digital transformation in public sector health and social care services - Kuoppakangas Päivikki; Stenvall Jari; Kinder Tony; Lindfors Juha; Talonen Antti (Elsevier, 2025)
This paper provides new insights into perceptions of the meaningfulness of work of service professionals and how it is constructed in the new context of digitalised health and social care long-term services, intended to offer cocreated services. It elucidates the criteria evaluating the success of the digital services from the viewpoint of the service professionals. The paper presents case data from advanced digitalised services in Finland based on indepth interviews with eighteen service professionals. Citing a broad range of literature, the paper carefully defines meaningfulness and co-creation in the context of long-term social and healthcare services and using a Vygotskian approach to social learning, it provides evidence of how context influences perceptions of successful change and of meaningfulness. In doing so, the paper suggests that the context for these digitalised services is best viewed from: (a) the stakeholder ecosystem, (b) the service context and (c) the service delivery framework. While most research on digitalized health and social care services focuses solely on the success or failure of the service, this paper adds to the body of knowledge around the impact of the meaningfulness of work for the professionals involved. The paper concludes with recommendations for influencing meaningfulness in relation to digital co-creation platforms in public sector health and social care services.